Synthesis and biological evaluation of N-(carbobenzyloxy)-l-phenylalanine and N-(carbobenzyloxy)-l-aspartic acid-β-benzyl ester derivatives as potent topoisomerase IIα inhibitors. Issue 12 (15th June 2017) - Han, Xiaoyan; Zhong, Yifan; Zhou, Guan; Qi, Hui; Li, Shengbin; Ding, Qiang; Liu, Zhenming; Song, Yali; Qiao, Xiaoqiang
Graphical abstract: Highlights: 13 compounds as topoisomerase IIα inhibitors were designed and synthesized. Evaluated for topo I and IIα inhibitory activity, antiproliferative activity. Molecular docking studies were investigated. Compounds showed selective topoisomerase IIα inhibition. 5b showed best antiproliferative activity, topoisomerase IIα inhibitory activity. Abstract: A new series of thirteen N -(carbobenzyloxy)-l -phenylalanine and N -(carbobenzyloxy)-l -aspartic acid- β -benzyl ester compounds were synthesized and evaluated for antiproliferative activity against four different human cancer cell lines: cervical cancer (HeLa), lung cancer (A549), gastric cancer (MGC-803) and breast cancer (MCF-7) as well as topoisomerase I and IIα inhibitory activity. Compounds (5a, 5b, 5e, 8a, 8b ) showed significant antiproliferative activity with low IC50 values against the four cancer cell lines. Equally, compounds5a, 5b, 5e, 5f, 8a, 8d, 8e and8f showed topoisomerase IIα inhibitory activity at 100 μM with5b, 5e, 8f exhibiting potential topoisomerase IIα inhibitory activity compared to positive control at 100 μM and 20 μM, respectively. Conversely compounds5e, 5f, 5g and8a showed weaker topoisomerase I inhibitory activity compared to positive control at 100 μM. Compound5b exhibited the most potent topoisomerase IIα inhibitory activity at low concentration and better antiproliferative activity against the four human cancer cell lines. The molecular interactions between compounds5a –5g, 8a –8f and the topoisomerase IIα (PDB ID:1ZXM ) were further investigated through molecular docking. The results indicated that these compounds could serve as promising leads for further optimization as novel antitumor agents.